Case Report: Posterior Thoracic Window in the Presence of Pleural Effusion in Critical Care Medicine: One More Chance to Image the Aortic Valve - Mantovani, Francesca; Benfari, Giovanni; Barbieri, Andrea; Manca, Francesco; Guiducci, Vincenzo; Navazio, Alessandro; Clavel, Marie-Annick (Frontiers in Cardiovascular Medicine, 2022)
Good quality echocardiographic images in the setting of critical care medicine may be difficult to obtain for many reasons. We present a case of an 85-year-old woman with acute pulmonary edema and pleural effusion, where transthoracic bedside echocardiographic examination raised a suspicion for significant aortic valve disease. However, given the orthopneic decubitus of the patients, the quality of images was poor. To increase the accuracy of diagnosis, a posterior thoracic view through the pleural effusion in the sitting position was used. This view allowed the diagnosis of mixed aortic valve disease (aortic stenosis and regurgitation) and the quantification of valve disease through multiparametric criteria as recommended by current guidelines. The posterior thoracic view, when feasible, may provide a useful option in the assessment of cardiac structures and further diagnostic information in technically difficult echocardiographic examinations.